Test Report – SRIA Class L Mesh Slab Tests (Volume 1 - 3) - Chandler, Ian; Lloyd, Natalie (Department of Civil Engineering, Curtin University, 2012)
The Test Report is arranged in three volumes: Volume 1 (of 3): Report contains a comprehensive written account of the research and describes, in addition to the construction and testing regime details, the salient observations and test results with reference to Volumes 2 (of 3): Plates and Volume 3 (of 3): Figures. Volume 2 contains a comprehensive visual record of the behaviour of the slabs throughout each stage of loading. Each plate is explained in the text of Volume 1 and includes images of the development of crack patterns throughout the stages of loading of the slab tests on the exposed surfaces. Volume 3 contains a comprehensive graphical representation of the test data obtained throughout the load stages for all slabs tested. The types of graphs include load–deflection, load–time, variation in moment– time, slab longitudinal deflection profiles, crack widths, strains in concrete and reinforcement, rotations and reaction frame deflections.